On the coexistence and complementarity of Chinese translation methods of English metrical poetry - Li Chongyue,; Gao Shaole,; Gu Sen,; Feng Ruizhen, (Penerbit UKM, 2010)
The Chinese translation of English metrical poetry has a history of more than one hundred years, but it is still controversial on how to translate English metrical poetry into Chinese. Chinese translators have hitherto devised three methods to render English metrical poetry: sinolization, liberalization, and poetic form transplantation. Translators practicing the methods of sinolization and liberalization belong to the group in favor of spiritual resemblance. Translators who follow the method of poetic form transplantation belong to the group in favor of formal resemblance. It is quite obvious that the two groups have disagreement on the translation standard or guiding principle. Actually the translation standards of the two groups can coexist, and the translation methods under the guidance of these different translation standards can coexist and complement each other. It is impractical and impossible to use one Chinese translation method or standard to guide all the Chinese translation practice, and the diverse Chinese translation methods of English metrical poetry can coexist and complement each other in the foreseeable future.